Synthesis and characterization of micro/nanoparticles of poly(vinylalcohol-co-vinylcinnamate) derivatives - C. Luadthong (2018)
Various poly(vinylalcohol-co-vinylcinnamate) derivatives including poly(vinylalcohol-co-vinylcinnamate), poly(vinylalcohol-co-vinyl-4-methoxycinnamate), poly(vinylalcohol-co-vinyl-2,4-dimethoxycinnamate) and poly(vinylalcohol-co-vinyl-2,4,5-trimethoxycinnamate) were synthesized by grafting poly(vinylalcohol) with appropriate cinnamoyl groups. The self-assembly of grafted products into spherical micellar nanoparticles was performed, and particles were analyzed using dynamic light scattering, scanning electron microscopy, and transmission electron microscopy.1H NMR analyses of the well-dispersed micellar particle suspensions and polymer solutions indicated that the hydroxyl groups of the polymer were on the outer surface of the spheres, while the cinnamoyl moieties were buried inside the spheres forming crystalline structure. Polymer with a higher degree of cinnamoyl substitution gave smaller particles upon self-assembly. Variations in particle sizes obtained from PV(OH) grafted with cinnamoyl derivatives of different methoxy substitution on the benzene ring were observed. Molecular weight of the polymers did not significantly affect nanoparticle size and morphology. In addition, self-assembly of the poly(vinylalcohol-co-vinylcinnamate) derivatives into hollow reverse micellar microparticles of uniform size was also demonstrated.1H NMR spectrum of the reverse micellar micro-particle suspension indicated that the cinnamoyl moieties were not in a crystalline state. © 2008 Elsevier Ltd. All rights reserved.